Early institutional provision in Scotland for disabled children - Iain Hutchison (Scottish Journal of Residential Child Care, 2004)
By the end of the nineteenth century, a wide range of institutional provision was well-established in Scotland as it was across much of Europe and beyond. While adults were often the initial focus of such provision, specialist institutions for children were also established. However, for disabled children, their introduction might be regarded as haphazard.